ANALISIS SEMIOTIKA FOTOGRAFI â€œALKISAHâ€ KARYA RIO MOTRET (RIO WIBOWO) - Huda, Muhamad Miftahul; Hamim, Hamim; Wibowo, Judhi Hari (representamen, 2018)
This research is motivated by the development of photography as a medium of visualcommunication to create an image as well as provide and deliver a message. One photographerIndonesia, Rio photographed create photographic works of folklore Indonesian theme with the title"Once upon a time". He tried to revive the appeal of folklore with a different delivery. This studyaimed to describe the meaning of photos contained in an image photographed Rio theme Alkisahwork. This study focused on five object Once among others Nyi Roro Kidul, Jonggrang, Pitung, MalinKundang, Kasarung. The theory used is the theory of Roland Barthes Semiotics which consists of twostages marking the denotation stage as the first stage and second stage stage connotation as inmeaning. The method used research methods used in this research is qualitative and descriptive. Datacollection techniques with in-depth interviews, observation, and documentation. The study found thatthe meaning of denotation and connotation of the five themes examined Alkisah photos bring backmemories and convey folklore through advances in visual and multimedia.Keywords : Semiotic, Photography, Alkisah, Works Rio Motret